A regional renaissance? The shifting geography of internal migration under COVID-19. Issue 4 (2nd October 2022) - Borsellino, Rosabella; Bernard, Aude; Charles-Edwards, Elin; Corcoran, Jonathan
ABSTRACT: Since the beginning of the COVID-19 pandemic there has been interest in the migration of city-dwellers to regional areas to escape lockdowns and movement restrictions, yet evidence of a 'regional renaissance' in Australia remains anecdotal. This paper aims to quantify the current and future dynamics of the COVID-19 pandemic on the levels, patterns and drivers of migration to and from Australian cities and regions. Results show a 7% drop in the rate of migration between Greater Capital City Statistical Areas in 2020 compared to the previous year, with record net gains in regional areas facilitated by a 9% decrease in departures rather than an increase in arrivals from cities. Our forecasts suggest that net gains to regions will slow down after 2022, but remain higher than pre-pandemic levels in New South Wales, Queensland, South Australia, and Tasmania because of a sustained increase in arrivals. Regional Western Australia and the Northern Territory will continue to record net losses, while net gains to regional Victoria are predicted to be lower than pre-COVID-19 because of an increase in departures. These patterns have important implications for population projections and policies regarding the attraction and retention of internal migrants to Australia's regions.